Implementación de una Pulidora Metalográfica para el Laboratorio de Materiales de la Universidad Antonio Nariño Sede Puerto Colombia, Colombia (2021)
The teaching processes of mechanical engineering require different laboratory equipment, according to the areas of emphasis and depth. For the area of engineering materials, in relation to the analysis of microstructures in metallic, plastic, ceramic and composite materials, equipment such as: test tube cutters, test tube polishers and optical, electronic and similar microscopes are required. Knowledge of the microstructures of metals allows the engineer to infer mechanical, chemical, electrical and other properties, which correlate with the correct application of the material for a required service. Aspects like. Grain size, shape, orientation, segregation, non-metallic inclusions, are relevant to the application and investigation of metals. An auxiliary and important equipment to manufacture the specimens that are observed in microscopes is the metallographic polisher. With this equipment, students and researchers can process the surface of the test tube that is subjected to observation in the microscope to a degree of surface finish called the mirror, an essential condition to proceed with the chemical attack prior to the observation, processing and analysis of microstructures resulting from heat treatments and manufacturing processes. For this reason, the objective of the project is "to implement a metallographic polishing machine for the materials laboratory at the Antonio Nariño University". In this degree work, developed at the Antonio Nariño University, Puerto Colombia headquarters, a metallographic polishing machine is designed, implemented and commissioned, an equipment that fulfills the function of giving the final finish to surfaces of metallic specimens to which it is intended to obtain their microstructural profile through the microscope. Taking as a reference the polishing conditions defined by the American standard ASTM E - 03 - 17. The implemented design allows a safe use of the equipment, providing high quality mirror polishes that allow obtaining the microstructure of the analyzed metals, improving the capacity of the materials laboratory and the quality of the teaching provided. The final document develops an operation and maintenance manual, the information necessary to facilitate the operation and sustained use of the equipment. The applied design approach is the canonical methodology that ensures to define and meet the technical requirements that these equipment must satisfy as defined by the ASTM standard to consider them appropriate for this type of application